The role of antibody-drug conjugates in the treatment of lung cancer - Zlatanova, Tanya; Changalova, Aynura; Janzic, Urska (Frontiers in Oncology, 2026)
Over the las0t decades, lung cancer treatment has improved immensely, mainly due to the incorporation of new targeted treatments and immunotherapy. A relatively new and potentially highly effective class of drugs, antibody-drug conjugates (ADCs), has been introduced to the clinical setting and is currently under intense investigation, alone and in combination with other molecules. This study aims to summarize the latest data on ADCs for lung cancer treatment and to analyze their potential, toxicity profile, and challenges.